WATERTOOL™: AN AUTOMATED SYSTEM FOR HYDROLOGICAL INVESTIGATIONS WITH APPLICATION AT THE AREA OF KATO SOULI (NE ATTICA, GREECE) - Sotiropoulos, P.; Tzanis, A.; Sideris, G. (Bulletin of the Geological Society of Greece, 2007)
Surface and groundwater resources are important assets for the economic and social welfare of the population of a given area; they are renewable and with proper management, they contribute substantially to sustained development. Unfortunately, the expansion of industrial and agricultural activities lead to increasing withdrawal of water from the aquifers, excessive use of pesticides and fertilizers and (frequently illicit) disposal of industrial waste. This results in rapid reduction in the quantity and quality of water reserves. There's a compelling call for the development of advanced and inexpensive means to monitor the quantitative and qualitative characteristics of water resources. In response to such requirements, as specified by Directive 2000/60 of the European Commission, TerraMentor E.E.I.G. has spearheaded the development of a multi-channel sensor and system to measure up to 15 physical and chemical parameters (pollutant concentration) facilitating the evaluation of water quality in real time (Watertool™). The system uses the Ion-Selective Electrode technology, which is thoroughly described. Its effectiveness is demonstrated with an application in the area of Kato Souli (NE Attica), which suffers from intense salination (seawater intrusion) and pollution of the aquifer. It is shown that the Watertool is an inexpensive, accurate and fast method to map the quality of groundwater reserves and assist aquifer managers in making effective decisions.